DOWNY MILDEW OF WHEAT IN MEXICO - RUPERT; BORLAUG (Escuela Nacional Ciencias Químicas, CD MEXICO, DF, MEX, 1979)
Identified as Sclerospora macrospora
PROC ZOO SOC LONDON
Keywords: DOWNY MILDEW, WHEAT, MEXICO; CIENCIAS DE LA VIDA; QUIMICA FISICA; QUIMICA INTERFASES